The economics and econometrics of the energy-growth nexus - Menegaki, Angeliki (Academic Press, 2018)
The Economics and Econometrics of the Energy-Growth Nexus recognizes that research in the energy-growth nexus field is heterogeneous and controversial. To make studies in the field as comparable as possible, chapters cover aggregate energy and disaggregate energy consumption and single country and multiple country analysis. As a foundational resource that helps researchers answer fundamental questions about their energy-growth projects, it combines theory and practice to classify and summarize the literature and explain the econometrics of the energy-growth nexus. The book provides order and guidance, enabling researchers to feel confident that they are adhering to widely accepted assumptions and procedures.